What is the first step in solving the system shows using the elimination method?
A. Multiply each term in 3y – x = 9 by 12.
B. Multiply each term in 3y – x = 9 by -12,
C. Rewrite the equations so like variable terms are in the same order.
D. Add the corresponding sides of each equation.


  1. Answer:
    Step-by-step explanation:
    I’m not sure what you mean by those steps mean but here is how I would answer using the elimination method:
    3x – 12y = 5
    minus (each term separately: 3x – 3x, -12y – -y, and 5 – 9)
    3x – y = 9
    This eliminates the 3x and = -11y = -4
    You can then simplify from there and get y = 4/11


Leave a Comment